2020
DOI: 10.32890/ijms.27.1.2020.7524
|View full text |Cite
|
Sign up to set email alerts
|

Corporate Brand Image of Islamic Bank in Malaysia: Antecedents and Consequence

Abstract: The role of corporate brand image in influencing the survival of companies has never been underestimated. Because of this, this study intends to examine the antecedents and the consequence of corporate brand image towards customer behaviour. A model proposing firms and non-firms communication as the antecedents and loyalty as the consequence was proposed. One hundred and sixty-eight (168) questionnaires were collected and data was analysed based on the Partial Least Square-Structural Equation Modeling (PLS-SEM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 70 publications
0
5
0
Order By: Relevance
“…Within this cluster of research, various studies explore the impact of bank image on the intention to use Fintech services (Ab Hamid et al ., 2020; Rahi et al ., 2020; Liu et al ., 2023), the relevance of green banking practices on establishing a green image (Alshebami, 2021), and the effects of image, brand, and quality on customer loyalty within Sharia or Islamic banks (Amin et al ., 2013; Riyadi, 2021; Ab Hamid et al ., 2023).…”
Section: Cluster Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Within this cluster of research, various studies explore the impact of bank image on the intention to use Fintech services (Ab Hamid et al ., 2020; Rahi et al ., 2020; Liu et al ., 2023), the relevance of green banking practices on establishing a green image (Alshebami, 2021), and the effects of image, brand, and quality on customer loyalty within Sharia or Islamic banks (Amin et al ., 2013; Riyadi, 2021; Ab Hamid et al ., 2023).…”
Section: Cluster Analysismentioning
confidence: 99%
“…see Abd-El-Salam et al ., 2013) by considering it a significant predictor of customers’ behavioral intentions (Ryu et al ., 2012) or explained it by focusing specifically on financial institutions (such as bank image) (e.g. see Bravo et al ., 2009; Hamid et al ., 2020; Warsito et al ., 2022).…”
Section: Cluster Analysismentioning
confidence: 99%
“…Based on the above concerns, consumer evaluations will be positive when CSR activities are consistent because it reduces the efforts of consumers in searching for additional information. Word-of-mouth and word of mouse play a significant role in influencing the image compared to the Islamic bank communication (Hamid et al, 2020). How CSR can become a technique to establish trust, redress name and restore brand reputation have not been adequately explored.…”
Section: Figurementioning
confidence: 99%
“…Therefore, customers’ perceptions of a bank and its attributes as brand image consists of sum associations inside the mind that has some classical effects including satisfaction (Rahi et al , 2020), intention to use (Awan et al , 2018), selection (Narteh and Braimah, 2019) and more importantly it is considered as relational partner (Fournier, 1998). Literature review in bank marketing studies revealed that researchers applied four terminological definition of image namely bank image (Yavas and Shemwell, 1996), brand image (Pinar et al , 2016), corporate image (Omoregie et al , 2019; Iqbal et al , 2018) and corporate brand image (Ab Hamid et al , 2020). However, all mentioned nominal concepts could refer to a more general concept (bank image) due to the fact that researchers have a tendency to use them interchangeably (Bravo et al , 2012) and to use Brand as Company metaphor (De Chernatony, 2010, p. 35).…”
Section: Theoretical Frameworkmentioning
confidence: 99%